Web-based New Student Registration System using User-Centered Design Method - Farhan, Burait; Razilu, Zila; Rifai, Sitti Najmia (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
This study aims to design and develop a web-based new student registration system using the User-Centered Design (UCD) approach. The UCD method is applied to ensure that the resulting system meets user needs, enhances efficiency, and provides an optimal user experience. This system is designed as a solution to the challenges of manual registration at MIS Hubbul Wathan Toli-Toli, such as document accumulation, long queues, and difficulties in data management. The research stages include observation, interviews, literature review, wireframe design, and design evaluation through usability testing. The test results indicate that the system demonstrates good to excellent usability across the dimensions of Learnability, Efficiency, Memorability, Errors, and Satisfaction, based on a Likert scale analysis (1–5). The system enables a more efficient registration process, reduces data entry errors, and improves user convenience. This study contributes to the development of an information system tailored to user needs and opens opportunities for further enhancements, such as integrating additional features and improving user experience through continuous evaluation.